A Systematic Approach to the Development of Novel Therapeutics for Lung Cancer Using Genomic Analyses. Issue 2 (8th May 2013) - Daigo, Y; Takano, A; Teramoto, K; Chung, S; Nakamura, Y
<x xml:space="preserve">Abstract</x> Molecularly targeted drugs for cancer therapy represent a therapeutic advance, but the proportion of patients who receive clinical benefit is still very limited. We present here the rationale and initial results of our program to define molecules involved in lung carcinogenesis with the goal of identifying new therapeutic targets and/or predictive biomarkers for drug response. We have used gene expression analysis of 120 lung cancers followed by RNA interference, tumor‐tissue microarray analysis, and functional analyses to systematically distinguish potential target molecules specifically expressed in cancer cells. Through this approach, we have identified oncoproteins that provide the starting point for the development of therapeutic antibodies, dominant negative peptides, small‐molecule inhibitors, and therapeutic cancer vaccines. We believe that the approach we describe should result in new molecularly targeted therapies with minimal risk of adverse events. Clinical Pharmacology & Therapeutics (2013); 94 2, 218–223. doi:10.1038/clpt.2013.90